Code-switching as a linguistic resource in an EFL context at a language center in Mexico - Tatiana Estefanía Galván de la Fuente (English Language Education Study Program, Faculty of Education and Teacher Training, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, Indonesia, 2023)
This study explores code-switching (CS) as an interactional resource by learners in an EFL classroom in a predominantly monolingual context of Mexico could provide university students with a useful resource in language learning. The research aim is to identify and analyze the codeswitching interactional patterns that the students use to participate in the classroom such as reiteration, equivalence, floor-holding and socializing. In order to analyze these ways, observation sessions were carried out as these depictions demonstrated what was taking place in the EFL classroom. Field notes are used to triangulate data; therefore, a more in-depth and rich analysis is brought forth as to how these resources are used. Accordingly, classroom data is analyzed using an applied Conversation Analysis approach. This case study is part of a PhD project that explores the linguistic practices of nine students from two intermediate EFL classes. Both observations and field notes reveal that learners´ draw on CS for carrying out learning activities, negotiate meaning, as it is a supporting element in the communication of information and in the learners’ social interaction. Therefore, the study suggests that CS serves for communicative purposes in a way that is exploited as a tool for transference of meaning.